IMF Staff Papers, Volume 52, Special Issue, IMF Conference in Honor of Michael Mussa. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2005)
This paper focuses on expectations for the American economy focused on the likelihood of secular stagnation, which continued to be debated throughout the post-war period. Concerns rose during the late 1960s and early 1970s about rapid population growth smothering the potential for economic growth in developing countries were contradicted when, during the mid- and late-1970s, fertility rates began to decline rapidly. In policy-oriented institutions (and in most businesses and individual decision making), policymaking decisions are often guided by projections and forward-looking indicators. The case of Michael Mussa has been one of great anticipation, and of great accomplishment, and all the early optimistic forecasts about him have turned out to be correct. Within the sphere of economics, undoubtedly the most famous and widely used forecast-one, incidentally, that thus far has often been incorrect-is that based on the Malthusian doctrine of the relationship between resources and population.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet